Kolaviron protects against benzo[a]pyrene-induced functional alterations along the brain-pituitary-gonadal axis in male rats (2015)
Exposure to benzo[a]pyrene (B[a]P) is well reported to be associated with neurological and reproductive dysfunctions. The present study investigated the influence of kolaviron, an isolated biflavonoid from the seed of Garcinia kola, on functional alterations along the brain-pituitary-gonadal axis in male rats exposed to B[a] P. Benzo[a]pyrene was orally administered at a dose of 10 mg/kg alone or orally co-administered with kolaviron at 100 and 200 mg/kg for 15 consecutive days. Administration of B[a]P significantly (p < 0.05) decreased plasma levels of pituitary hormones namely follicle-stimulating hormone (FSH) and prolactin but increased luteinizing hormone (LH) by 47%, 55% and 20.9%, respectively, when compared with the control. The significant decrease in gonadosomatic index (GSI) was accompanied by significant decrease in testosterone production and sperm functional parameters in the B[a]P- treated rats. Moreover, B[a]P - treated rats showed significant elevation in the circulatory concentrations of pro-inflammatory cytokines and oxidative stress indices in the brain, testes and sperm of B[a]P-treated rats. Light microscopy revealed severe necrosis of the Purkinje cells in the cerebellum, neuronal degeneration of the cerebral cortex, neuronal necrosis of the hippocampus and testicular atrophy in B[a]P-treated rats. Kolaviron co-treatment significantly ameliorated B[a]P mediated damages by suppressing pro-inflammatory mediators and enhancing the antioxidant status, neuroendocrine function, sperm characteristics and improving the architecture of the brain and testes in B[a]P-treated rats. The findings in the present investigation highlight that kolaviron may be developed to novel therapeutic agent against toxicity resulting from B[a]P exposure.